Tactics of Preoperative Examination of Patients with Infective Endocarditis Complicated by Acute Heart Failure - Koltunova, Hanna B. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Background. Management of patients with infective endocarditis (IE) has changed rapidly in recent years with improvements in diagnostic procedures and early aggressive surgical treatment. The annual incidence of IE in high-income countries has reached 9 cases per 100,000 population. Approximately half of patients with IE require surgical treatment due to severe complications, the most common of which is acute heart failure (AHF), which occurs in 40–60% of cases. Clinical scenarios of IE are often complex, requiring rapid diagnostic measures and early appointment of surgical intervention. The aim. To determine the preoperative algorithm of diagnostic and therapeutic measures in the presence of signs of AHF in patients with IE. Materials and methods. The basis of this study is the clinical data of 311 patients with active IE who underwent examination and treatment at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medi- cal Sciences of Ukraine from 01/01/2019 to 10/22/2021. The diagnosis of IE was established in accordance with Duke Endocarditis Service criteria proposed in 1994. The average age of the studied patients was 47.9 ± 3.83 (19 to 77) years. Results. In order to determine the degree of AHF at the preoperative stage, all the patients were divided into 4 groups according to the New York Heart Association functional classification. Preoperative clinical data of IE patients with signs of AHF comprised the basis for functional class IV (59 [18.9%] cases) and formed the studied group. For preoperative diagnosis of AHF, cardiohemodynamic data was obtained based on the results of echocardiographic parameters and level of N-terminal pro-B-type natriuretic peptide (NTproBNP). In order to improve the diagnosis of AHF, tactics of preoperative examination of patients with IE were developed. In our study, the following echocardiographic examination results were indicative in the diagnosis of IE complicated by heart failure: detection of vegetations on the leaflets of the left heart valves, end-diastolic index >94.3 ml/m2, end-systolic index >40.8 ml/m2, pulmonary artery pressure >50 mm Hg. The main biochemical marker of AHF in the group of patients with IE was the threshold level of NTproBNP greater than 7473.7 pg/ml. Identified changes in cardiohemodynamic and biochemical indicators became independent indications for hospitalization in the intensive care unit and emergency preoperative preparation. Conclusions. During hospitalization of patients with IE to the cardiosurgical center, the basis of the effectiveness of the provided care is the timely diagnosis of complications of the underlying disease. Based on the results of the work, the protocol for preoperative AHF diagnosis was developed. Critical levels of biochemical and hemodynamic indicators in patients with IE became an independent indication for hospitalization to the intensive care unit and emergency preoperative management. The early start of intensive care for AHF in IE is a fundamental factor that might influence the choice of treatment strategy.